An innovative correlation of PV and Fuel cell Microgrid Power generating System - et. al., Srinivasa Rao Sura, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Recently revolting centres,banks domain is the Microgrid,the intensification, declined costs, revealed involvement and evolving concession are its advantages. A Microgrid method of working is the self-sustained system which contributes power to the load unaccompanied to integrate with the utility grid. Microgrid have solicitations in faraway and unreachable places where the utilizers survive in the absence of power supply. In secluded and hinterland places the power connection is not technologically attainable,at such kind of areas microgrid meet the stipulation of these places. On the basis of the customer urge this system is composed of a Photovoltaic energy and a Solid oxide fuel cell (SOFC) energy conjointed to configure a microgrid system which is fasten to the load. The impetus of this paper is to design the components of a PVFC microgrid system needed to accomplish the electricity demand for the secluded places.This combines the improvement of small power distributed sources and also to enhance their technologies. Microgrid is an emerging technique and it This microgrid scheme manifests of distributed generators, energy storage devices, loads and interfaces. A persistant amount of power generation cannot be provided by most of the DGs so, a conventional controlling strategy is required to maintain the microgrid to operate at steady state and reliable.